(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2020)
A case study is to provide evidence of the feasibility, acceptance, and benefits of a computer game-assisted repetitive task practice platform (G-RTP) in Upper extremity (UE) motor function of a child with Cerebral Palsy (CP). Method: 4 year old left spastic CP was provided an individualized game-assisted therapy of 16 weeks. Outcome measures included PDMS-2, QUEST, computerized assessment of a broad range of object manipulation tasks. Results: Findings demonstrated the feasibility and acceptability of the G-RTP program for use by children with UE motor impairment Conclusion: The findings are positive and support a future definitive RCT needed to prove the efficacy and applicability